Clinical case of preservation of teeth vitality during treatment of initial pulpitis - D. A. Ostanina; A. M. Fulova; Yu. A. Mitronin; A. V. Mitronin (Эндодонтия Today, 2023)
Diagnosis and treatment of pulp disease is one of the leading and widespread problems in dentistry. Clinicians are often faced with a dilemma when treating vital teeth with deep carious lesions and the development of reversible inflammation in the pulp tissue: whether to perform minimally invasive treatment to maintain pulp viability or to perform vital extirpation to prevent pulp necrosis, its further infection and prevention of apical periodontitis. To date, researchers and clinicians report that clinical recovery of the pulp with viable new bioactive materials is observed in 90% of cases provided that the inflammatory process in the pulp is diagnosed in the stage of reversibility. This article presents a clinical case of initial pulpitis treatment of teeth 1.5, 1.6 with the pulp-preserving method: direct pulp capping with bioactive cement Biodentine (Septodont). In the dynamics of observation after 1, 6, 12, 18 months teeth were asymptomatic and a favorable prognosis of the therapy was observed.